Muscle quality correlates with hearing thresholds: a cross-sectional analysis - Jeon, Young-Jee; Lee, Ji Ho; Kang, Byung Chul; Kwon, Joong Keun (Frontiers in Aging, 2026)
IntroductionMuscle health, including muscle volume, is an independent risk factor for physical disability and metabolic disorders. Although low muscle mass has been associated with hearing loss, the association between computed tomography (CT)-derived muscle quality and hearing has not been explored.MethodsThis cross-sectional study examined associations between abdominal body composition and hearing thresholds in 7,774 adults (4,537 men and 3,237 women) aged ≥40 years undergoing routine health check-ups. Abdominopelvic CT and pure-tone audiometry were performed, and total abdominal muscle area (TAMA), normal-attenuation muscle area (NAMA), low-attenuation muscle area (LAMA), intermuscular adipose tissue (IMAT), visceral fat area (VFA), and subcutaneous fat area (SFA) were quantified from CT-based muscle quality maps. The best-ear pure-tone average (PTA, 1–4 kHz) was analyzed as the loge-transformed PTA. Multivariable linear regression models were fitted separately for men and women, adjusting for age, cardiovascular risk factors, and lifestyle variables.ResultsThe loge-transformed LAMA index was independently associated with hearing in both sexes. Each 10% increase in the loge-transformed LAMA index corresponded to an estimated 0.11 dB worsening of PTA in men and 0.14 dB worsening in women. In women, TAMA, NAMA, and VFA indices were associated with PTA; these associations were confined to women in their 50s and 60s in decade-stratified analyses. No abdominal body composition indices were significantly associated with hearing thresholds in any age group among men.ConclusionsThese findings suggest that abdominal body composition is associated with age-related hearing loss (ARHL), particularly in midlife women, and highlight skeletal muscle health as a potential target for hearing preservation.